THE CHARACTERISTICSOF TEACHERSCOLLEGE - Barrientos Jiménez, Elsa Julia (2014)
The university teacher is one who cultivates knowledge, is outstanding researcher because it has to be updated in education or in your workplace, to conduct investigations is kept updated. The functions and features the university teacher as well as actions of teachers are considered the XXI century statistical tables and hypothesis test are presented.